Makna Ikon Kristus Bagi Umat Kristen Poso - Shanti Rualemba; I Gede Supradnyana (Jurnal Teologi Pambelum, 2026)
The Icon of Christ is an important religious symbol for Christians in Poso, Central Sulawesi. In the post-conflict era of social and religious that had occurred in the Poso region, the icon of Christ became one of the forms of restoring the identity of the faith of the people. Research on the meaning of the icon of Christ in the lives of Poso Christians, as far as the author knows, has not been much explored from the theological and spiritual side as well as its function in the life of faith in the local context. Therefore, the author conducted this study to trace and write it down. This study was conducted qualitatively with a descriptive approach through interviews and field observations. As a result of observations and interviews, it was found that the icon of Christ is understood by people as a spiritual means that strengthens the relationship with God. The icon of Christ becomes a means of inner healing for parishioners, a spiritual window as an experience of faith, as well as part of faith education in the family. The icon of Christ has gone beyond the visual function. The icon becomes a symbol of the presence of God who merges with the struggles and hopes of his people ini everyday life.